Le Bundesrat. La protection des intérêts des Länder selon la Loi fondamentale allemande - Bothe, Michael (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
After dealing with the West German Bundersrat in a double-chamber system, the author, following the Basic Law of the country, depicts the varied powers of this Chamber. The participation of the Bundersrat in federal legislation is examined through its suspensive veto over every bill adopted by the first chamber — the Bundestag. The Bundersrat also has the power to approve certain categories of Bills. The participation of the Bundersrat in the federal administration, contentious powers and the nomination process are ideas also developed in this article. The author examines the political role of the Chamber and shows that the Bundersrat has a counterbalancing effect between the Bundestag and the federal government. The importance of the roles of the parties in developing the political position of the Bundersrat is also discursed herein. Professor Bothe concludes by saying that the Bundersrat is an important element of West German cooperative federalism and wonders if exporting this institution to Canada would be a wise move.